2016
DOI: 10.1159/000448396
|View full text |Cite
|
Sign up to set email alerts
|

Topical Timolol Maleate 0.5% for Infantile Hemangioma: Its Effectiveness Compared to Ultrapotent Topical Corticosteroids - A Single-Center Experience of 278 Cases

Abstract: Background: Infantile hemangioma (IH) may have implications on parental distress and cosmetic disfigurement. To date, ultrapotent corticosteroids are used as a treatment of choice for superficial IH. However, due to their side effects and sometimes lack of IH regression, it is necessary to find alternative topical therapies. Timolol maleate 0.5% solution and gel are nonselective β-blockers that could inhibit proliferation and trigger regression of IH. Objective: To evaluate the efficacy of topical ultrapotent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 46 publications
4
34
0
1
Order By: Relevance
“…The efficacy of TXE treatment was largely similar to that of TM treatment for superficial lesions (57.7% vs 56.3% good response; p = 0.21) and mixed lesions (53.8% vs 40% good response; p = 0.35). This agrees with earlier findings of Danarti et al , who concluded that TM and TXE treatment had similar therapeutic efficacy for superficial IH lesions. Earlier age of treatment initiation was associated with better therapeutic response (62.8% good response with treatment initiation <3 mos vs 35.3% with treatment initiation >6 mos; p = 0.18).…”
supporting
confidence: 93%
“…The efficacy of TXE treatment was largely similar to that of TM treatment for superficial lesions (57.7% vs 56.3% good response; p = 0.21) and mixed lesions (53.8% vs 40% good response; p = 0.35). This agrees with earlier findings of Danarti et al , who concluded that TM and TXE treatment had similar therapeutic efficacy for superficial IH lesions. Earlier age of treatment initiation was associated with better therapeutic response (62.8% good response with treatment initiation <3 mos vs 35.3% with treatment initiation >6 mos; p = 0.18).…”
supporting
confidence: 93%
“…6 In addition to the significant efficacy of topical timolol observed in our center, 4 several other reports support this observation. Oral propranolol, a beta-blocker, may cause systematic adverse events and therefore close monitoring of the patients is required.…”
Section: Discussionsupporting
confidence: 72%
“…Compared with other topical medication, timolol maleate is considerably superior to topical corticosteroids, regardless of its form, whether in solution or gel. 6 In addition to the significant efficacy of topical timolol observed in our center, 4 several other reports support this observation. One multicenter retrospective cohort study revealed that among all the 731 patients treated with topical timolol, the best response occurred in superficial IH of less than 1-mm thickness, and adverse events were noted only in 3.4% of the patients.…”
Section: Discussionsupporting
confidence: 72%
“…In a retrospective study by Qiu et al, timolol 0.5% eye drop and imiquimod 5% cream achieved equivalent clinical efficacy, but fewer side effects were observed in patients treating with topical timolol (16). Danarti et al compared the effectiveness of topical corticosteroids and timolol maleate 0.5% solution or gel (21). Effectiveness of topical timolol maleate 0.5% solution or gel was significantly better than topical corticosteroids, but there was no difference in IHs treating with timolol solution versus gel (21).…”
Section: Discussionmentioning
confidence: 99%
“…Danarti et al compared the effectiveness of topical corticosteroids and timolol maleate 0.5% solution or gel (21). Effectiveness of topical timolol maleate 0.5% solution or gel was significantly better than topical corticosteroids, but there was no difference in IHs treating with timolol solution versus gel (21). A cohort study showed that timolol 0.5% gel forming solution was more effective than timolol 0.1% gel forming solution, suggesting that drug concentration is an important predictor for clinical responses (22).…”
Section: Discussionmentioning
confidence: 99%